Two pediatric cases of Pneumocystis jirovecii pneumonia diagnosed by polymerase chain reaction of gastric lavage. Issue 6 (June 2019) - Takei, Haruka; Ishiwada, Naruhiko; Hishiki, Haruka; Takeshita, Kenichi; Naito, Sachiko; Endo, Mamiko; Shimojo, Naoki
Abstract: Detecting Pneumocystis jirovecii by bronchoalveolar lavage or lung biopsy is the gold standard for diagnosis of P. jirovecii pneumonia (PJP); however, these techniques are not always applicable in children because of their high invasiveness. We report two pediatric cases of PJP diagnosed by polymerase chain reaction (PCR) of gastric lavage that were successfully treated. To date, there are no reported cases of using PCR of gastric lavage to diagnose PJP. On the day of PJP onset, both the infants required respiratory support and infiltrative shadows were observed in both lung fields on chest radiography. Furthermore, their (1 → 3)-β-D glucan levels were elevated. P. jirovecii was detected by PCR of gastric lavage and trimethoprim-sulfamethoxazole was administered for 3 weeks, following which their condition improved. They were long-term steroid users, but without any prophylaxis. PCR of gastric lavage in cases of suspected PJP may help in confirming the diagnosis in children who have mild to moderate airway symptoms, or have difficulty with invasive examination like bronchoscopy.